4с(с-2)-(с-4) ( С-4) в квадрате 3(y-1)+6y (y-1) в квадрате

0 голосов
25 просмотров

4с(с-2)-(с-4) ( С-4) в квадрате

3(y-1)+6y (y-1) в квадрате


Алгебра (19 баллов) | 25 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

1) 4c^2-8c-c+4=4c^2-9c+4

2)(c-4)^2=c^2-8c+16

3)3(y-1)+6y=3y-3+6y=9y-3

4)(y-1)^2=y^2-2y+1

 

 

 

 

 

 

(224k баллов)
0 голосов

4с(с-2)-(с-4)^2=4c^2-8c-(c^2-8c+16)=4c^2-8c-c^2+8c-16=3c^2-16   (^2-в квадрате)

3(y-1)^2+6y =3(y^2-2y+1)+6y=3y^2-6y+3+6y=3y^2+3=3(y^2+1) 

(1.3k баллов)